Improving Basic Literacy of Slow Learner Students Through the Discovery Learning Model Assisted by Reading Applications - Desi, Zefania; Setiowati, Yunisa; Ruby, Arcivid Chorynia (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: This study aims to improve the basic literacy skills of Slow Learner students through the application of the Discovery Learning model assisted by reading applications. Background Problem: The problem examined in this study is the low basic literacy skills of Slow Learner students, especially in reading long words, recognizing double consonant letters, and understanding reading content. Conventional learning approaches have proven less effective for students with special needs, so more adaptive strategies are needed. Novelty: The novelty of this research lies in combining Discovery Learning strategies with interactive digital media aimed specifically at students with special needs, which is rarely discussed in depth in the context of basic education. Research Methods: This study used the Classroom Action Research (PTK) method which was carried out in three cycles with the subject of one Slow Learner student in grade V elementary school. Data were obtained through observation, interviews, tests, and documentation. Data analysis in this study was carried out using quantitative and qualitative approaches. Findings/Results: The results showed an increase in test scores from 40 (pre-cycle) to 60, 70, and 85 in cycles I to III. Students' learning activities also increased from moderate to good category. Conclusion: Thus, the Discovery Learning model assisted by reading applications is proven effective in improving the basic literacy skills of Slow Learner students and can be an appropriate and sustainable alternative in inclusive learning.